(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Roger Williams, the pioneer of religious freedom in America The challenges of the contemporary dramatic religious persecutions in different corners of the globe are similar to what the pioneer of the religious liberty in America, Raoger Williams experienced nearly four centuries ago. This paper explores the main ideas that Williams developed in his most important work, The Bloudy Tenet of Persecution for Cause of Conscience. His contribution to correct the usage of the Scripture to support the actual persecution of the non-puritans of the seventeenth century America is outstanding. Rather, Williams proves that the principle of religious liberty and that of the separation between church and state are deeply rooted in the Word of God.